Similar neuroendocrine and metabolic effects of sulfate-chloride sodium-magnesium mineral waters "Myroslava" and "Khrystyna" of Truskavets’ spa in healthy female rats - Hrytsak, Myroslava; Popovych, Daria; Badiuk, Nataliya; Hrytsan, Ivanna; Zukow, Walery (Journal of Education, Health and Sport, 2021)
Background. In order to expand the hydro-mineral base of Truskavets’ spa by diluting brine (130 g/L), two new sulphate-chloride sodium-magnesium mineral waters "Myroslava" (5 g/L) and "Khrystyna" (10 g/L) were created. This report is the first in a series of experimental studies of their physiological activity in line with the concepts of neuroendocrine-immune complex and functional-metabolic continuum. Materials and Methods. Experiment was performed on 50 healthy female Wistar rats 220-300 g divided into 4 groups. Animals of the first group remained intact, using tap water from drinking ad libitum. Rats of the control group for 6 days administered a single tap water through the tube at a dose of 1,5 mL/100 g of body mass. The rats of the main groups received the water "Myroslava" and "Khrystyna". The day after the completion of the drinking course in all rats assessed the state of autonomous regulation by parameters of the HRV. The plasma levels of the hormones of adaptation were determined: corticosterone, triiodothyronine and testosterone (by the ELISA); as well as electrolytes, nitric metabolites, lipid peroxidation products and antioxidant enzymes as well as cholesterol, glucose, amylase and middle mass molecules. Most of the listed parameters of metabolism as well as 17-ketosteroids were determined in daily urine. In the adrenal glands the thickness of glomerular, fascicular, reticular and medullar zones was measured. Results. To identify exactly those parameters, the set of which three groups of animals differ significantly from each other, the information field of the registered parameters was subjected to discriminant analysis. The program included in the model 6 endocrine and 11 metabolic parameters, as well as glomerular filtration. Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets’ spa have similar neuroendocrine and metabolic effects on healthy old female rats significantly different from daily water.